Aging resistance of bio-epoxy jute-basalt hybrid composites as novel multilayer structures for cladding. (15th January 2017) - Fiore, V.; Scalici, T.; Badagliacco, D.; Enea, D.; Alaimo, G.; Valenza, A.
Abstract: Aging resistance of jute reinforced laminates is compared with two jute/basalt hybrid laminates prepared with different stacking sequences (i.e., sandwich and intercalated configuration). To this aim, composites are exposed to cyclic conditions comprising hygrothermal stress and UV radiation to promote an accelerated aging, for a period of 84 days. Specimens of each laminate are tested after 14, 28, 56 and 84 days, respectively. Quasi-static flexural tests, Charpy impact tests and dynamic mechanical tests are performed according to international ASTM and ISO standards. Furthermore, scanning electron microscopy and differential scanning calorimetry are used to evaluate the morphology of the laminates and the curing residual heat, respectively. Results showed that hybrid laminates exhibit higher impact energy and flexural properties than jute laminates, in addition to greater aging resistance. Moreover, hybrid laminates with sandwich-like configuration show improved aging tolerance in comparison to those with an intercalated configuration.